Resting distal to aortic pressure ratio and fractional flow reserve discordance affects the diagnostic performance of quantitative flow ratio: Results from an individual patient data meta‐analysis. Issue 5 (1st June 2020) - Westra, Jelmer; Eftekhari, Ashkan; Tu, Shengxian; Campo, Gianluca; Escaned, Javier; Winther, Simon; Matsuo, Hitoshi; Qu, Xinkai; Koltowski, Lukasz; Chang, Yunxiao; Liu, Tommy; Yang, Junqing; et al.
Abstract: Objective: To evaluate the diagnostic performance of quantitative flow ratio (QFR) related to fractional flow reserve (FFR) and resting distal‐to‐aortic pressure ratio (resting Pd/Pa) concordance. Background: QFR is a method for computation of FFR based on standard coronary angiography. It is unclear how QFR is performed in patients with discordance between FFR and resting pressure ratios (distal‐to‐aortic pressure ratio [Pd/Pa]). Materials and Methods: The main comparison was the diagnostic performance of QFR with FFR as reference stratified by correspondence between FFR and resting Pd/Pa. Secondary outcome measures included distribution of clinical or procedural characteristics stratified by FFR and resting Pd/Pa correspondence. Results: Four prospective studies matched the inclusion criteria. Analysis was performed on patient level data reaching a total of 759 patients and 887 vessels with paired FFR, QFR, and resting Pd/Pa. Median FFR was 0.85 (IQR: 0.77–0.90). Diagnostic accuracy of QFR with FFR as reference was higher if FFR corresponded to resting Pd/Pa: accuracy 90% (95% CI: 88–92) versus 72% (95% CI: 64–80), p < .001, and sAUC 0.95 (95% CI: 0.92‐0.96) versus 0.73 (95% CI: 0.69–0.77), p < .001. Resting Pd/Pa and FFR discordance were related to age, sex, hypertension, and lesion severity. Conclusion: Diagnostic performance of QFR with FFR as reference is reduced for lesions with discordant FFR (≤0.80) and resting Pd/Pa (≤0.92) measurements.